Can Energy Democracy Thrive in a Non-democracy? - Delina, Laurence L. (Frontiers in Environmental Science, 2018)
This paper argues that energy democracy could manifest in terms of public engagement at the community level, free of state intervention, government fostering, and donor support, even in locations where governments have been in flux from a democracy to a non-democracy. In currently non-democratic Thailand, for example, public engagement on community energy transitions had occurred, were sustained, and proved to be durable over time. The spaces of deliberation, created and nurtured by Thai citizens in this community, had become effective sites for navigating and negotiating the ebbs and flows of democratically organized sociotechnical energy transitions. This paper further argues that these spaces for public engagement had revealed that energy democracy is collective, cultural, consequential, co-produced, co-existent, and critical phenomenon that can be used to shore up an energy democracy framework.